Mental toughness for athletes in sport: Scopus bibliometric analysis - Anindra Guspa; Wildan Haru Pradani; Amin Akbar; Rahmadianti Aulia; Silvi Juwita; Rizal Kurniawan; Devi Lusiria; Mario Pratama (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Psychological aspects are gaining popularity in sport as athletes strive for success. One psychological factor that is critical to supporting success is mental toughness. Mental toughness is defined as an athlete's ability to stay focused, calm, and think positively in the face of pressure during competition